Determinants of MSMEs Access to WIBAWA Credit (Universitas Negeri Semarang, 2022)
Capital need is a challenge experienced by MSME. Semarang city government provides an innovation of capital access assistance to MSMEs with Revolving Fund Loan Program, namely WIBAWA Credit. MSMEs status is feasible and not bankable, due to non-fulfillment of 5C principle. This study credit determinant analysis aims to develop a study of granting WIBAWA credit patterns. Secondary research data were obtained from Dinkop & UMKM Kota Semarang and PERUMDA BPR Bank Pasar Kota Semarang by taking a sample of 600 WIBAWA Credit application data for 2017-2019. Binary Logistic Regression analysis results through IBM SPSS Statistics 22 software show that there are differences in gender of business owners, business size, and business age in decision to grant WIBAWA credit, while credit history variable has no effect. Dinkop & MSMEs Kota Semarang need to improve creditworthiness of female business owners, micro-Enterprises, and start-up/new early businesses so that they have more opportunities to qualify for credit financing. MSMEs that re-apply for WIBAWA Credit can also be given a faster assessment process period and larger disbursement ceiling, but still, pay attention to credit repayment factor by debtor. Kebutuhan modal menjadi tantangan yang dialami pemilik UMKM. Pemerintah Kota Semarang memberikan bantuan akses modal kepada UMKM dengan Program Pinjaman Dana Bergulir yaitu Kredit WIBAWA. Penelitian ini bertujuan untuk mengembangkan kajian terhadap pola pemberian Kredit WIBAWA. Data penelitian sekunder diperoleh dari Dinkop & UMKM Kota Semarang dan PERUMDA BPR Bank Pasar Kota Semarang dengan mengambil sampel 600 data pengajuan Kredit WIBAWA periode tahun 2017-2019. Hasil analisis Binary Logistic Regression melalui software IBM SPSS Statistics 22 menunjukkan bahwa terdapat perbedaan jenis kelamin pemilik usaha, ukuran usaha dan umur usaha dalam keputusan pemberian Kredit WIBAWA, sementara variabel riwayat kredit tidak memberikan pengaruh.